BANTUAN PANDUAN “ONE TO FIVE” - Riyanto, Edi (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2018)
The purpose of this study was to determine the increase in learning outcomes of cartwheel floor gymnastics in physical education through the application of learning modifications with the help of “one to five” guide. This research method uses classroom action research consisting of two cycles, each of which has four steps: Planning, Implementation, Observation, and Reflection. The research subjects were students of class VIIID SMP Negeri 3 Mrebet even semester 2017/2018 school year as many as 28 students consisting of 16 male students and 12 female students. Data collection techniques use test results, and observation. The analytical technique used for quantitative data is comparative descriptive analysis. The qualitative data of the observations using qualitative descriptive analysis. There was an increase in the results of learning the movements of the cartwheel gymnastics after the action of cycle I and cycle II where the average value of learning the floor gymnastics before the action of the movement was 70.00, the average value in the first cycle was 79.07, and the average score the average cycle II is 80.54. The indicator of the success of this study is 85% or 24 students get the value of learning outcomes equal to or more than the KKM 72. From these targets it turns out that student learning outcomes are exceeded that is 89.29% or 25 students exceed the KKM, so the number of students whose learning outcomes are above or the same as the KKM increased significantly.